Modificação da superfície de óxidos de ferro por dextrana derivatizada para aplicações em liberação de fármaco - Piazza, Rodolfo Debone [UNESP] (2014)
The modification of the iron oxide nanoparticles surface has attracted interest of the scientific community due to the large number of applications of this material in different areas of knowledge. The biomedicine is one area in growing improvement in the use of nanoparticles, because the synergy between the magnetic properties and the biocompatibility of the modified surface allows the use these materials in diagnostic and treatment of diseases, as well as the controlled drug delivery. The application of magnetic field to guide the magnetic nanoparticles conjugated with drugs is one promising technique, capable of reduce the problems associated with the traditional way of drugs administration, increasing the welfare of the patients on these treatments. The present work consists in the functionalization of magnetic nanoparticles based on iron oxide by derivatized dextran, using the miniemulsion polymerization method, for doxorubicin release studies. The magnetic nanoparticles of maghemite were obtained from the magnetite oxidation synthesized by coprecipitation, while the dextran was derivatized by the glycidyl methacrylate with the intention of anchor vinyl groups on the surface. These materials were characterized by spectroscopic techniques, as infrared, Raman, magnetic resonance of H1 e C13. The iron oxide was encapsulated in the derivatized dextran through inverse polymerization by miniemulsion. In this phase, some parameters of synthesis, as the type and the surfactant concentration, monomers fraction and percentage of iron oxide, were varied to obtain a stable system, allowing its use in biomedical application. The core@shell system obtained showed incorporation efficiency over 80% of doxorubicin, although the drug release percentage from diffusion was low during the analyzed period.